(untitled) (Faridpur Medical College Journal, 2017)
Low birth weight (LBW) is one of the main predictors of infant mortality. The global incidence of LBW is around 17%, although estimates vary from 19% in the developing countries like Bangladesh to 5-7% in the developed countries. About one third of delivery is low birth weight. LBW is generally associated with situations in which uterine malnutrition is produced due to alterations in placental circulation. There are many known risk factors, the most important of which are socio-economic factors, medical risks before or during gestation and maternal lifestyles. However, although interventions exist to prevent many of these factors before and during pregnancy, the incidence of LBW has not decreased. Faridpur Med. Coll. J. Jan 2017;12(1): 40-46